Paediatric acute disseminated encephalomyelitis followed by optic neuritis: disease course, treatment response and outcome. (9th March 2018) - Wong, Y. Y. M.; Hacohen, Y.; Armangue, T.; Wassmer, E.; Verhelst, H.; Hemingway, C.; van Pelt, E. D.; Catsman‐Berrevoets, C. E.; Hintzen, R. Q.; Deiva, K.; Lim, M. J.; Rostásy, K.; et al.
Abstract : Background and purpose: Acute disseminated encephalomyelitis followed by optic neuritis (ADEM‐ON) is a rare demyelinating syndrome that is different from multiple sclerosis and neuromyelitis optica spectrum disorder. The aim of this study was to describe the disease course, treatment response and outcome of children with ADEM‐ON. Methods: Children of <18 years of age were identified from six countries of the EU Paediatric Demyelinating Disease Consortium. Patients fulfilled the diagnostic criteria for ADEM followed by at least one ON. Anti‐myelin oligodendrocyte glycoprotein (MOG) antibodies were tested in all patients. Results: In this study of 17 patients (nine boys) with ADEM‐ON, anti‐myelin oligodendrocyte glycoprotein (MOG) antibodies were identified in 16 patients. Age at onset was 6.1 years (interquartile range, 5.1–9.2 years). Twelve patients received oral prednisolone and 10 received maintenance immunosuppression (e.g. azathioprine, intravenous immunoglobulins, Rituximab). During a follow‐up of 5.3 years (interquartile range, 1.8–10.2 years), 54 relapses occurred with a median of 3 relapses per patient (range, 1–9 per patient). Patients relapsed on all treatments but no relapses occurred on a prednisolone dose >10 mg/day. Visual and cognitive residual deficits were common in this group. Conclusions: Acute disseminated encephalomyelitis followed by optic neuritis is an anti‐MOG antibody‐associated relapsing disorder that can have a heterogeneous disease course. Patients were refractory for maintenance immunosuppression and appeared to be corticosteroid‐dependent. Further international collaborations are now required to unify guidelines in this difficult‐to‐manage group of patients.